Analisis Ketelitian Pengukuran Beda Tinggi Menggunakan Metode Waterpass dan Total Station - Samman, Daffa Sinatrya; Patanduk, Nelson; Ridwan, Ridwan; Natsir, Taufiq; Gusfiadi, Gusfiadi (Indonesian Journal of Fundamental Sciences, 2025)
Abstract. This study discusses the accuracy of height-difference measurements using the Waterpass and Total Station methods. The method employed is a literature review based on a descriptive, qualitative-comparative approach. The results indicate that the Waterpass method provides higher accuracy compared to the Total Station, with smaller standard deviations and lower closure errors. Nevertheless, the Total Station excels in measurement time efficiency. The choice of method should be adjusted to the project’s needs; Waterpass is suitable for limited areas requiring high accuracy, while Total Station is appropriate for broader coverage and time efficiency. Keywords: High Difference Measurement, Total Station, Waterpass